Community Steered Research: A Conceptual Model for Tackling Power Symmetries, Cognitive Justice, and Integrated Knowledge in Research - Kazemi, Fatemeh; Gonzalez Benson, Odessa; Juárez, Nicolás; Palova, Katerina (The Canadian Journal of Action Research, 2026)
The prominence of community-based research is growing, driven by its commitment to a social justice, diversity, and equity approach. However, challenges persist in actualizing the transformative potential and the promise of community-based research approaches, as community-academic partnerships are strained by structural issues such as funding mechanisms, power dynamics, and diverging priorities and temporalities. This paper proposes Community Steered Research and offers a novel conceptual model on the research process to address these issues, drawing from the experience of conducting research in the Canadian immigrant-serving settlement sector. The model flips the academic-community hierarchy, proposing that research be initiated and steered by the community, rather than the university. This model argues that embeddedness, relationality, and dynamism are essential to what is commonly termed ‘community-based’ research, if it is to move towards meaningful application and its transformative aims.